TANGGUNG JAWAB DEBITUR TERHADAP PENGALIHAN OBJEK JAMINAN FIDUSIA TANPA PERSETUJUAN KREDITUR (Studi Putusan Pengadilan Negeri Kisaran Nomor 05/Pdt.G/2013/PN.Kis) - DIAN STEVANY TONGLI (PREMISE LAW JURNAL, 2017)
In the fiduciary guarantee, the object that becomes the fiduciary object is still in debtor’s possession, not in the creditor’s, so the handing over of ownership of the object is carried out without handing over the object physically.The Article 23 in the Law No. 42/1999 on Fiduciary Guarantee, a debtor must not transfer, pawn or rent to another party the object of the Fiduciary Guarantee which is not a supply, unless there is a written approval from the creditor.The results show that the title of the fiduciary object in the fiduciary agreement is transferred to the creditor, while the property is still kept by the debtor. In other words, the debtor is not legalized to transfer the fiduciary object to the third party and any transfer made without the creditor’s approval becomes null and void. The liability of the debtor who has transferred the fiduciary object is to indemnify the restoration into the former condition because he has committed an unlawful act, he is convicted by the penal law and sentenced by maximum of 2 (two) years’ imprisonment and fined by maximum of IDR 50,000,000.- (fifty million Rupiah) pursuant to Article 36 of the Law No. 42/1999 on Fiduciary Guarantee. Keywords: Liability, Transfer, Fiduciary Guarantee